Potential of Edible Insects in Indonesia as Nutritious Local Food - Nasir, Syifa Qolbiyah (Universitas Ahmad Dahlan, 2025)
Amid the expansion of the global population, the demand for sustainable, high-quality food rises. Edible insects provide an innovative and promising alternative to traditional sources of animal protein. Abundant types of insects are recognized as safe to eat worldwide and various edible insect-based food products have been widely developed globally. This research is a narrative review that identified articles using keywords in English and Bahasa. Searches were conducted on Google Scholar, Scopus, Science Direct, and MDPI. Twenty out of 106 articles were selected for the final used in the review. The review emphasizes the diverse range of edible insect species present in Indonesia and their remarkable nutritional benefits, which include energy, carbohydrate, protein, fat, and micronutrients. These insects have been integrated into local delicacies, leading to the creation of some innovative products such as pempek, cookies, sausages, and meat substitutes. However, the wider acceptance of edible insects in everyday diets is still hindered by religious, cultural, food safety, and perceptual obstacles. Further multidisciplinary research is needed to make edible insects a viable solution for a sustainable food system in the future.